Oceanic loading of wildfire-derived organic compounds from a small mountainous river - Hunsinger, Glendon B.; Mitra, Siddhartha; Warrick, Jonathan A.; Alexander, Clark R. (My University, 2008)
Small mountainous rivers (SMRs) export substantial amounts of sediment into the world's oceans. The concomitant yield of organic carbon (OC) associated with this class of rivers has also been shown to be significant and compositionally unique. We report here excessively high loadings of polycyclic aromatic hydrocarbons (PAHs), lignin, and levoglucosan, discharged from the Santa Clara River into the Santa Barbara Channel. The abundance of PAHs, levoglucosan, and lignin in Santa Barbara Channel sediments ranged from 201.7 to 1232.3 ng gdw−1, 1.3 to 6.9 μg gdw−1, and 0.3 to 2.2 mg per 100 mg of the sedimentary OC, respectively. Assuming a constant rate of sediment accumulation, the annual fluxes of PAHs, levoglucosan, and lignin, to the Santa Barbara Channel were respectively, 885.5 ± 170.2 ng cm−2 a−1, 3.5 ± 1.9 μg cm−2 a−1 and 1.4 ± 0.3 mg per 100 mg OC cm−2 a−1, over ∼30 years. The close agreement between PAHs, levoglucosan, and lignin abundance suggests that the depositional flux of these compounds is largely biomass combustion-derived. To that end, use of the Santa Clara River as a model for SMRs suggests this class of rivers may be one of the largest contributors of pyrolyzed carbon to coastal systems and the open ocean. Wildfire associated carbon discharged from other high yield fluvial systems, when considered collectively, may be a significant source of lignin, pyrolytic PAHs, and other pyrogenic compounds to the ocean. Extrapolating these methods over geologic time may offer useful historical information about carbon sequestration and burial in coastal sediments and affect coastal carbon budgets.
Copyright 2008 by the American Geophysical Union.
Keywords: Biogeochemical cycles; Biogeochemical processes; Biogeochemical modeling; Carbon cycling; Contaminant biogeochemistry; Organic biogeochemistry